The 12-13 year-old skaters free programs of contents and peculiarities of judging - Stoletova, V. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: The most important problem in ice figure skating is the inconsistency of judging the competition. In an attempt to solve the problem, the International Skating Union developed a system of refereeing which, in 2004 on the 51th congress ISU, had been approved as the official and obligatory application on all international competitions since the 2005-2006 season. Acceptance of the given system of refereeing should affect the contents and structure of competitions, that has predetermined the purpose of the present research - to analyse the contents of free programs 12-13 year-old skaters and the peculiarity of its judging. Methods The contents of 22 skaters of 1994-1995 free programs who took part in a tournament have been analysed. And also reports of competitions were processed. Results Research of the contents of competitive compositions has shown, that on a set of jumping elements of the program 6 ladies mismatched rules, since in four cases the quantity of jumps exceeded the demanded 7, and 2 more girls have not shown either a combination, or a sequence. On a set of spins all competitive programs corresponded to the ordered requirements. During refereeing competitions the technical committee estimates the complexity of spins, steps and spiral sequences, appropriating a certain level of complexity from the first to the fourth. The element most often estimated by a technical committee as the highest level of complexity (the fourth), is the spiral sequence (32 %). It is necessary to specify, that one of the given elements has not been estimated in connection with discrepancy to the ordered requirements. All executed paths of steps have received the lowest first level (100 %). Only the combination of spins from all elements of the given group have been estimated on the fourth level (14 %). While perfoming competitive programs the judge estimates the quality of elements. Average value GOE of skaters free compositions ranged from-0,56 up to 0,02 points. The analysis of quality of performance of jumps shows that skaters executed the double Lutz better (average value GOE on group has made-0,13 a point). The largest discrepancy on quality of judging has been recognized in two turns (-1,46). Lower level ability sportsmen executed the xel in one turn and double Salchow. Marks for components of the programs (table 2) differed slightly (on 0,21 points) and on the average made 2,84 points. The highest point occurred for skating skills, the lowest - for linking movements. This study also examined the marks skaters received for execution of the program. The essential difference in the sum of marks between skaters occupying the 1st, 2nd and 21st and 22nd places is visible. For women 13 (59,1 %) of the marks for other components of the program exceed the marks for technique. For 5 girls (22,7 %) marks for technique and components were similar. . Conclusions The free skating programs of 8 women mismatched the ordered requirements. The judges estimated the paths of steps of all 22 skaters, were appropriately at the first level. The most inaccurate area associated with the quality jumping element according to the judges, was recognized as the double xel. The highest average points for an athlete at a given age is associated with the first com ponent of the program - skating skills; the least - for the second - linking movements. For the majority of athletes (59 %) the mark for components of the program exceeded a mark for elements of technique.